Integrating scRNA-seq and bulk RNA-seq to explore the differentiation mechanism of human nail stem cells mediated by onychofibroblasts - Fang, Xia; Zhou, Jiateng; Yang, Yating; Li, Dawei; Wang, Bin (Frontiers in Cell and Developmental Biology, 2024)
Nail stem cell (NSC) differentiation plays a vital role in maintaining nail homeostasis and facilitating digit regeneration. Recently, onychofibroblasts (OFs), specialized mesenchymal cells beneath the nail matrix, have emerged as potential regulators of NSC differentiation. However, limited understanding of OFs' cellular properties and transcriptomic profiles hinders our comprehension of their role. This study aims to characterize human OFs and investigate their involvement in NSC differentiation. We isolated human OFs and characterized their mesenchymal stem cell-like phenotypes. To delineate the molecular features of human OFs, bulk RNA-seq was conducted on three samples of OFs and control fibroblasts from human nail units. The analysis results highlight the role of OFs in coordinating human nail development. Through integrated analysis with scRNA-seq data from human nail units, we identified BMP4 as a pivotal signal for OFs to participate in NSC differentiation through mesenchymal-epithelial interactions, with the TGF-beta pathway possibly mediating this signal. OFs synthesized and secreted more BMP4 than control fibroblasts, and BMP4 derived from OFs induced NSC differentiation in a co-culture model. Recombinant human BMP4 activated the TGF-beta pathway in NSCs, leading to cell differentiation, while the BMP type I receptor inhibitor LDN193189 attenuated this effect. This study characterizes the cellular and molecular features of human OFs, demonstrating their ability to regulate NSC differentiation via the TGF-beta signaling pathway. These findings establish a connection between the dermal microenvironment and NSC differentiation, suggesting the potential of OFs, in conjunction with NSCs, for developing novel therapies targeting nail and digit defects, even severe limb amputation.